El aporte del Ṛg-Veda a la doctrina no dualista (advaita vedānta) según Śaṅkara - Hernández Quiroz, Anselmo (El Colegio de México, 2022)
Śaṅkara accepts the Veda as the orthodox scriptural source for the inquiry into both dharma and brahman. Various studies have already analyzed the textual interrelationships woven by the author mainly around the upaniṣad in support of his non-dualistic doctrine (advaita vedānta), as well as the interpretation strategies that he employs. However, fewer works have explored the textual relationships in his commentaries on other canonical Vedic sources, such as the Ṛg-Veda. This article mainly focuses on identifying the Ṛg-Veda's contribution to the non-dualistic doctrine (advaita vedānta) according to Śaṅkara, initially by researching two connections between Śaṅkara’s commentary on the Brahma-Sūtra and the Ṛg-Veda.